ROLE OF 0.2% BIO-ADHESIVE CHLORHEXIDINE GEL IN REDUCING INCIDENCE OF ALVEOLAR OSTEITIS - Shad, Samia; Shah, Syed Majid Hussain; Tahir, Muhammad Waheed; Geelani, Syeda Rabia Rahat; Khan, Saqib Mehmood; Abbasi, Masroor Manshad (Journal of Ayub Medical College Abbottabad, 2018)
Background: Alveolar osteitis is a frequent postoperative complication of third molar surgery. A number of preventive methods have been tried. Chlorhexidine is most widely used antiseptic which is thought to be helpful to prevent alveolar osteitis. The objective of this study was to evaluate role of 0.2% bio-adhesive chlorhexidine gel in reducing incidence of alveolar osteitis after surgical removal of mandibular third molars which causes extra monetary burden on the patients in the form of several follow up visits. Methods: A randomized clinical trial was performed in the Dental Section, Ayub Medical College, Abbottabad. Approval from ethical committee was obtained. Total 180 patients were randomly divided into Group A in which patients received 0.2% bio-adhesive chlorhexidine gel and Group B where patients received placebo gel in the extraction socket after removal of mandibular third molar. Results: 0.2% bio-adhesive chlorhexidine gel used after mandibular third molar removal reduced incidence of alveolar osteitis by 10% in comparison to control group with statistically significant difference, i.e., p=0.044. Conclusion: 2.3 times reduction in the incidence of alveolar osteitis was observed after use of 0.2% bio-adhesive chlorhexidine gel. Keywords: Alveolar Osteitis; Dry Socket; Chlorhexidine Gel; Mandibular Third Molar